Analysis of implementing Realistic Mathematics Education principles to enhance mathematics competence of slow learner students - Listiawati, Nur; Sabon, Simon Sili; Siswantari; Subijanto; Wibowo, Slamet; Zulkardi; Riyanto, Bambang (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
One of the Education for Sustainable Development Goals is to provide equitable and inclusive access to quality education for all. However, some children with special needs, particularly slow learners, have yet to be able to enjoy inclusive and high-quality learning services. This research aims to enhance slow learners' competence by implementing the Realistic Mathematics Education Approach. It is descriptive qualitative research, with data collection techniques including focus group discussion, interview, and learning observation. The analysis involved comparing the principles of Realistic Mathematics Education in theory with those applied by teachers, as well as the learning approach used by teachers with those required by slow learners. The findings indicate that while some teachers have implemented learning based on the principles of Realistic Mathematics Education for all students, there needs to be more focus on interventions specifically tailored to the needs of slow learners. Furthermore, teachers still need to fully understand the services required by slow learners based on their unique characteristics. The implementation of Realistic Mathematics Education to meet the learning needs of slow learners in mathematics has primarily focused on activity and interactivity principles without emphasis on the understanding of concepts to enhance their competence.